The Rhizosphere Talk Show: The Rhizobia on Stage - Checcucci, Alice; Marchetti, Marta (Frontiers in Agronomy, 2020)
From bacterial quorum sensing to the signals of bees, communication is the basis of biotic interactions. Frequently, more than two organisms can take part in the speeches, resulting in a complex network of cross-talks. Recent advances in plant-microbe interactions research have shown that communication, both inter-kingdom and intra-kingdom, is shaped by a broad spectrum of factors. In this context, the rhizosphere (i.e., the soil close to the root surface) provides a specific microhabitat where complex interactions occur. The complex environment that makes up the rhizosphere can select for certain microbial populations, which are adapted to this unique niche. Among them, rhizobia have emerged as an important component of the rhizospheric microbiome. The aim of this review is to explore the components of such a rhizospheric Talk Show in the frame of the rhizobium-legume interactions. This symbiosis is a complex process that involves several signals that can be shaped by plant rhizospheric exudates and microbiome composition. The relationship established by rhizobia with other rhizospheric organisms, together with the influence of the environmental factors, results in their beneficial role on host plant health. Here, we resume research accounting strategies, molecules, and organisms that influence the place of rhizobia in the rhizosphere. The focus is on the most recent approaches for the study and subsequent exploitation of the diversity of the organisms. Indeed, the study of plant-microbes communication and evolution is fundamental to develop highly efficient inoculants able to reduce the use of fertilizers in agriculture.